A clinical therapeutic protein drug–drug interaction study: coadministration of denosumab and midazolam in postmenopausal women with osteoporosis. Issue 2 (13th March 2014) - Jang, Graham; Kaufman, Allegra; Lee, Edward; Hamilton, Lisa; Hutton, Shauna; Egbuna, Ogo; Padhi, Desmond
Abstract Drug–disease interactions involving therapeutic proteins that target cytokines and potentially impact cytochrome P450 (CYP) enzymes have been of increased interest to drug regulatory agencies and industry sponsors in recent years. This parallel‐group open‐label study evaluated the effects of the monoclonal antibody denosumab, an inhibitor of the cytokine RANKL, on the pharmacokinetics of the probe CYP3A4 substrate midazolam in postmenopausal women with osteoporosis. The pharmacokinetics of a 2 mg oral dose of midazolam was evaluated on days 1 and 16. Subjects in Group A received a 60 mg subcutaneous dose of denosumab on day 2, 2 weeks before the second midazolam dose, while subjects in Group B did not. For Group A (n = 17), point estimates for the ratio of least square means for midazolam exposures based on maximum observed plasma concentration (Cmax) and areas under the plasma concentration–time curve (AUCs) on day 16 versus day 1 ranged from 1.02 to 1.04 and 90% confidence intervals were within 0.80–1.25. No period effect was observed for Group B (n = 8). Midazolam and denosumab coadministration was safe and well tolerated. Inhibition of the cytokine RANKL by denosumab does not affect CYP3A4 in postmenopausal women with osteoporosis and will not alter the pharmacokinetics of drugs metabolized by this enzyme. These results are consistent with data suggesting that RANKL does not impact markers of inflammation and represent the first clinical data demonstrating a lack of effect on CYP3A4 of a therapeutic protein that is a cytokine modulator.